A novel method for evaluation of 2-ethylhexanol in octyl stearate by using gas chromatography technique - N.K.Sarthchandra Prakash; Jampala Balaji; Krishan Manaral (International Journal of Pharmacy and Analytical Research, 2022)
A new innovative method developed for determination of 2-Ethylhexanol in Octyl Stearate by gas chromatography using capillary column and flame ionization detection. This method may also be applicable for determination of 2- Ethylhexanol in cosmetic products. The determination of 2-Ethylhexanol was developed first time in Octyl Stearate. This method was validated as per ICH guidelines. This method was simple, specific, precise, linear, accurate, robust and ruggedness for analysis of 2-ethylhexanol in Octyl Stearate.